Implementation of Early Detection Activities for Stunting in Toddlers in Posyandu CMB Kotawaringin Timur Regency: Implementasi Kegiatan Deteksi dini Stunting Pada Balita di Posyandu CMB Kabupaten Kotawaringin Timur - Oki Alestari, Rena; Widia, Lidia; Safitri, Neneng (Journal of Community Empowerment for Multidisciplinary (JCEMTY), 2024)
Stunting is malnutrition that occurs when the baby is in the womb and at birth, but stunting only appears after the child is 2 years old. Stunting is caused by multi-dimensional factors. The most decisive intervention at 1,000 HPK (First 1000 Days of Life). (Ministry of Villages, Development of Disadvantaged Regions and Transmigration, 2017). The result is disruption of brain development, intelligence, physical growth disorders and metabolic disorders in the body (Ministry of Villages, Development of Disadvantaged Regions and Transmigration, 2017). The results of the 2013 Basic Health Research (Riskedas) showed that the prevalence of stunting reached 37.2%. The aim of this implementation is that mothers of toddlers have a better understanding of early detection of stunting in mothers of toddlers. The service method uses counseling using lectures, questions and answers, and examining the growth and development of toddlers using leaflets and giving awards to toddlers who have the best growth and development. Implementation activities will be carried out on June 19, 2024, at Posyandu CMB East Kotawaringin. The results of this community service activity can be said to be successful.  This can be observed in the level of attendance and activeness of participants. This activity took place in an orderly and good manner without experiencing significant obstacles. The follow-up that needs to be taken is to continuously monitor the growth and development of toddlers at Posyandu as an early detection of stunting in toddlers.